Development of problem and project-based learning syntax to improve vocational student learning outcomes - Akhyar, Muhammad; Ihsan, Fatihul; Suharno, Suharno; Tamrin, AG; Purwanto, Purwanto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
This study aims to: 1) Determine the needs of teachers and students for the development of learning models they face to overcome problems, 2) Formulate the feasibility of problem-based learning syntax, 3) Formulate the feasibility of Project-Based learning syntax, 4) Analyze the feasibility of problem-based learning model syntax and project-based learning in basic electricity and electronics at SMK Negeri 2 Sukoharjo. This study uses a research and development approach. The population in this study were all class X students of the Electronics Department at SMK Negeri 2 Sukoharjo for the 2020/2021 academic year with a sample of 64 students. Data collection techniques are using tests and non-tests. Data analysis used two-way analysis of variance (ANAVA). The results of the study show 1) The results of the analysis of the needs of teachers and students include: a) The results of the analysis of learning evaluations that are always demanded to be better; b) The results of teacher assessment analysis, so that teachers have many choices of learning variations and can make innovations in learning; c) Strategies obtained from data analysis, with details of operational programs as well as guidelines for implementing the strategic plan, duties and roles of the parties involved in the strategic plan, as well as evaluation and monitoring guidelines. 2) The syntax of the problem-based learning model goes through four phases: problem presentation, problem investigation, problem resolution and procedure evaluation. 3) The project-based learning model syntax includes: project startup, solution design, solution development, and presentation. 4) The results of the Wilcoxon test analysis, both problem-based learning and project-based learning, show that there is a difference in scores before and after being given treatment. So, it can be stated that problem-based learning methods and project-based learning are feasible to be used in improving student learning outcomes.